Recensiones - I. E.; Gloria Bodnar de Pilla; J. D.; L. A. S. I.; Luis de Sebastían (ECA: Estudios Centroamericanos, 1976)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 31, No. 338, 1976: 797-800.